Daddy's Little Matchmakers - Y'Barbo, Kathleen (Y'Barbo, Kathleen. Second time around., 2011)
Wanted: Wife And Mother. Veterinarian Eric Wilson is confounded by the classified ad his three young daughters have placed. The handsome widower is not in the market for a bride! But when the story of his little matchmakers hits the papers, would-be brides start swamping his waiting room. Despite them all, Eric finds himself drawn to the temp worker at the classifieds office: adorable free spirit Amy Spencer. Amy's been running for a while, and it's time she planted roots. Together, can Amy and Eric realize that trusting in God's plan is the sweetest surrender of all?